Analisis Penyaluran Zakat Mal Di Lembaga Amil Zakat (LAZ): Studi Kasus Insan Madani Provinsi Jambi - Putri Saumilia Lestari; Titin Agustin Nengsih; Solichah Solichah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Zakat is the fourth pillar of Islam in the form of maliyah ijtima'iyyah worship (economic and social aspects), one of the aims of which is to reduce the economic gap between rich and poor. To fulfill the zakat requirements, there are eight groups called